XueBiJing injection reduced mortality in sepsis patients with diabetes - Liu, Yan; Dai, Hengheng; Li, Yixuan; Yang, Tianyi; Zhang, Dandan; Hu, Chaoyue; Liu, Si; Feng, Zhiqiao; Zhang, Chi; Yang, Xiaohui (Frontiers in Pharmacology, 2025)
Introduction: Sepsis patients with diabetes are at a high clinical risk. It is well reported that XueBiJing®, an herbal-based injection, has good clinical benefits in sepsis individuals. However, there is not yet any relevant report about the efficacy and safety of XBJ in sepsis patients with comorbid diabetes. Methods: Two large randomized controlled clinical trials data were combined and post-hoc analyses were performed, XBJ-SAP (ChiCTR-TRC-13003534) and EXIT-SEP (NCT0323874). Sepsis patients with diabetes were further divided into XBJ-treated group and placebo group based on inclusion and exclusion criteria. The primary outcome (28-day mortality) and secondary outcomes (mortality in the ICU and in the post-randomization hospital, acute physiology and chronic health evaluation II (APACHE II) score, and sequential organ failure assessment (SOFA) score) were compared between the XBJ treatment and placebo groups in sepsis patients with diabetes status at baseline. Moreover, the occurrence of adverse events (AEs) was also assessed. Results: At the study baseline, a total of 378 sepsis patients (227 men [60.0%] and 151 women [40.0%]; mean [SD] age, 60.3 [11.1] years) were considered to have diabetes, of which 177 received XBJ and 201 received placebo administration. Among these sepsis patients with diabetes, mortality at 28 days was significantly lower in the XBJ group than in the placebo group (29 of 173 patients [16.8%] vs 56 of 198 patients [28.3%], P = 0.01) and the absolute risk difference was 11.5%(95%CI, 3.1% to 19.9%). Furthermore, there was no difference in the overall incidence of adverse events (AEs) when XBJ was used (24.4% [42 of 172 patients] vs 27.7% [54 of 195 patients]. Discussion: The present study underscores the pivotal role of XueBiJing® in modulating the immune response amongst sepsis patients suffering from diabetes mellitus, exploring the positive effects of XBJ on sepsis patients with diabetes mellitus. The efficacy and safety of XBJ compared with placebo were consistent with the overall trial findings, demonstrating that XBJ is efficacious in sepsis patients with diabetes and suggesting that there is no need for special safety precautions.